IoT-Based Smart Parking System with Real-Time Violation Detection and Alarm - Kamarudin, Amirul Syakir; Zainal, Zainab; Baharom, Md Nor Ramdon; Che Ros, Ziana (Multidisciplinary Applied Research and Innovation, 2025)
This paper presents an IoT-based Smart Parking System designed to modernize urban parking management using NodeMCU ESP32 and the Blynk platform. The system employs infrared sensors to control entry and exit barriers based on slot availability, and ultrasonic sensors for real-time tracking of occupied and available spaces. Each parking slot is linked to a specific car plate number through a QR code scanning process, ensuring authorized use. Unauthorized parking triggers a yellow LED and a buzzer alarm. The system features a user-friendly interface via the Blynk app, enabling remote monitoring and control. Users receive real-time notifications and can view slot status and control components remotely. Visual indicators include red LEDs for occupied slots and yellow LEDs with buzzers for parking violations. This smart parking solution enhances security, efficiency, and convenience in managing urban parking spaces.